Pemanfaatan Buah Pepaya Sebagai Upaya Peningkatan Pendapatan UMKM Anggota Kelompok Wanita Tani (KWT) - Al-Mubarok, M. Syauqi; Dwilestari, Ita (PASAI : Jurnal Pengabdian kepada Masyarakat, 2023)
This service invites people who still lack understanding in utilizing the abundant papaya yield. Armed with these problems, the purpose of this community service is to innovate and assist in the use of papaya fruit as an effort to increase the income of MSME Members of the Women Farmers Group (KWT) in Tiyuh Makarti, Tumijajar sub-district, West Tulang Bawang Regency. The method used in this service is the ABCD method as a means of community service approach with an orientation so that people have the power to recognize and utilize all the strengths and assets they have. The results of this dedication are crispy papaya products with attractive packaging and can be traded. Apart from that, this crispy papaya product can also be used as a souvenir so that it can increase the economic income of the community in general and KWT in particular.